Learning by doing - the didactic principle of German vocational training - Salazar, Yvonne Gabriele
This article presents the historical roots, referents, general criteria, goals and processes that characterize the German experience of learning by doing. The complete action model is described as one of the methodological axes, as well as the growing importance of learning by doing in the reform of German technical-vocational training during the last 20 years.